Management of a Board of Receivers in Banking Law - DĘBSKA, MONIKA MAGDALENA (Prawo Kanoniczne, 2013)
The appointment of a board of receivers is an instrument used in rehabilitation proceedings. The board of receivers originates from outside the bank but acts upon it from inside. The appointment of a board of receivers is an optional right of the Polish Financial Supervision Authority (Komisja Nadzoru Finansowego – KNF) and is applicable when the bank management board fails to submit a recovery program in accordance with art. 142(1) of the Banking Act or when the execution of that program is ineffective. The board of receivers is appointed by decision of the KNF. By virtue of art. 145(4) of the Banking Act, the KNF decision is administrative and, as such, can be appealed. The supervisory board of a bank subject to recovery measures may file an appeal to theSupreme Administrative Court within 7 days from the receipt of the decision. On the day the board of receivers is appointed all current governing authorities of the bank are suspended and replaced by the board of receivers, which takes over all their powers. This is why the board of receivers is often called “special bank authority”. Main tasks of the board of receivers consist in drawing up a rehabilitation program and agreeing it with the KNF, administering the execution of the program, and reporting the results achieved under the program to the KNF and the supervisory board at intervals of no less than three months.